2015
DOI: 10.1165/rcmb.2014-0230oc
|View full text |Cite
|
Sign up to set email alerts
|

DosS Is Required for the Complete Virulence of Mycobacterium tuberculosis in Mice with Classical Granulomatous Lesions

Abstract: Mycobacterium tuberculosis (Mtb) must counter hypoxia within granulomas to persist. DosR, in concert with sensor kinases DosS and DosT, regulates the response to hypoxia. Yet Mtb lacking functional DosR colonize the lungs of C57Bl/6 mice, presumably owing to the lack of organized lesions with sufficient hypoxia in that model. We compared the phenotype of the D-dosR, D-dosS, and D-dosT mutants to Mtb using C3HeB/FeJ mice, an alternate mouse model where lesions develop hypoxia. C3HeB/FeJ mice were infected via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 50 publications
5
64
3
Order By: Relevance
“…However, as other research groups have demonstrated, the standard mouse model of infection may not be suitable for teasing apart differences between strains based solely around DosR expression (57)(58)(59)(60). The granuloma-like cellular aggregations that form in the normal mouse lung appear not to develop areas of hypoxia; thus, any benefit to the bacteria that may arise due to continuous DosR regulon expression during the early phases of hypoxia development, for example, may not be observable within this model (61,62).…”
Section: Fig 6 the Dost Defect In Beijing Isolates Has No Impact On Tmentioning
confidence: 97%
See 1 more Smart Citation
“…However, as other research groups have demonstrated, the standard mouse model of infection may not be suitable for teasing apart differences between strains based solely around DosR expression (57)(58)(59)(60). The granuloma-like cellular aggregations that form in the normal mouse lung appear not to develop areas of hypoxia; thus, any benefit to the bacteria that may arise due to continuous DosR regulon expression during the early phases of hypoxia development, for example, may not be observable within this model (61,62).…”
Section: Fig 6 the Dost Defect In Beijing Isolates Has No Impact On Tmentioning
confidence: 97%
“…The granuloma-like cellular aggregations that form in the normal mouse lung appear not to develop areas of hypoxia; thus, any benefit to the bacteria that may arise due to continuous DosR regulon expression during the early phases of hypoxia development, for example, may not be observable within this model (61,62). In this regard, rabbits, guinea pigs, monkeys or the Kramnik mouse model may be more informative in future efforts aimed at comparing the effect of the Beijing versus non-Beijing DosR phenotypes on pathogenesis (57,59,60,62). The early delayedgrowth phenotype seen with the dosRS KO mutant suggests that this strain may be at a disadvantage early on after T-cell-mediated immunity develops in the lung.…”
Section: Fig 6 the Dost Defect In Beijing Isolates Has No Impact On Tmentioning
confidence: 99%
“…DosS acts as a redox sensor and DosT as a hypoxia sensor, illustrating the integration and differentiation of M. tuberculosis stress responses (105). Genetic disruption of the dosRST TCS results in reduced bacterial survival under low-oxygen conditions, in mouse models that develop hypoxic lesions, and in a nonhuman primate macaque model of infection (106)(107)(108)(109).…”
Section: Nonessential Tcss and Tfs: Special Forces Of The Stress Respmentioning
confidence: 99%
“…DosS and DosT have been shown to play an important role in the transition from the replicating state to NRP (15). Recently, Gautam et al (16) showed that DosS has a critical role in survival of M. tuberculosis in C3HeB/FeJ mice, whereas deletion of DosR and DosT gave rise to a growth curve comparable with that of wild-type M. tuberculosis. Kumar et al (17) demonstrated the importance of DosS by showing that induction of M. tuberculosis dormancy by CO depended primarily on sensing by DosS.…”
mentioning
confidence: 99%